Bridging BIM and LCSA to greening existing buildings : From a literature review to development of conceptual framework - Nur Syamimi, Zulkefli; Faizul Azli, Mohd-Rahim; Nurshuhada, Zainon (Institute of Physics, 2022)
Instead of looking into new building, this study shifted the focus to existing buildings considering the area has been less explored although the amount of energy released during the phase has significant influence towards sustainability impacts. Deriving from the situation, the purpose of this paper is to explore the potential of bridging BIM and the four-steps approach of Life Cycle Sustainability Assessment (LCSA) as an assisting tool to improve the performances of existing non-green buildings. To achieve aforementioned aim, an extensive literature review to identify the nexus between the two areas is done, as well as possibilities and challenges surfaced pertaining to the idea. Literature review process consists of several approaches including literature searching, classifying, and analysis were conducted. Based on literature review, a research gap is identified, and an initial conceptual framework is developed. The framework entails several areas of research that highlight on integrating LCSA approach, sustainability indicators and BIM functions. Apart from that, several implementation considerations to integrate both areas have been identified too. The conceptual framework presented in this study will serve as a basis to further develop an implementation framework that integrates BIM and LCSA to greening existing buildings. The final implementation framework is expected to assist project stakeholders including project manager (or facility manager), building owner, and consultants in making decision towards improving existing buildings' sustainable performance.